The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from Norway. (4th May 2017) - Kvaal, Erlend
Abstract: Although not a EU member, Norway is required to implement the EU Accounting Directive through its obligations under the EEA agreement. An expert group has prepared a draft law that will be decided upon by the legislator, most likely during 2017. The draft law has a strong orientation towards IFRS, which is evidenced in particular by the choice of IFRS for SMEs as the basis for Norwegian accounting standards.